2006
DOI: 10.1146/annurev.micro.60.080805.142139
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Competence Regulons as a General Response to Stress in Gram-Positive Bacteria

Abstract: Bacterial transformation, a programmed mechanism for genetic exchange originally discovered in Streptococcus pneumoniae, is widespread in bacteria. It is based on the uptake and integration of exogenous DNA into the recipient genome. This review examines whether induction of competence for genetic transformation is a general response to stress in gram-positive bacteria. It compares data obtained with bacteria chosen for their different lifestyles, the soil-dweller Bacillus subtilis and the major human pathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
439
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 359 publications
(454 citation statements)
references
References 135 publications
15
439
0
Order By: Relevance
“…Pneumococcal transformation requires transient differentiation to competence, during which expression of a specific set of genes (11) allows assembly of the transformasome (6). This dynamic machine involves both membrane and cytosolic proteins (including DprA and RecA), and promotes internalization, protection, and processing of transforming DNA into recombinants.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Pneumococcal transformation requires transient differentiation to competence, during which expression of a specific set of genes (11) allows assembly of the transformasome (6). This dynamic machine involves both membrane and cytosolic proteins (including DprA and RecA), and promotes internalization, protection, and processing of transforming DNA into recombinants.…”
mentioning
confidence: 99%
“…This dynamic machine involves both membrane and cytosolic proteins (including DprA and RecA), and promotes internalization, protection, and processing of transforming DNA into recombinants. Competence (or X-state) (11) is induced in exponentially growing cultures by a peptide pheromone, competence-stimulating peptide (CSP) (12), which ultimately activates the synthesis of an alternative sigma factor specific for competence (σ X ) (13). Induction of competence by some antibiotics and DNA-damaging agents (14) supports the view that CSP functions as an alarmone and that competence/ X-state constitutes an SOS substitute for S. pneumoniae (11).…”
mentioning
confidence: 99%
“…Claverys et al (2006) agreed with the idea that the particular state induced by ComE through ComX (named the X-state) is more extensive than competence. They also suggested that the X-state should be considered as a global response to alkaline stress rather than a quorum-sensing mechanism, despite its induction still being dependent on CSP.…”
Section: Discussionmentioning
confidence: 65%
“…It is assumed that a critical concentration of extracellular CSP is sensed by its receptor, the ComD histidine kinase, leading to autophosphorylation. The transfer of the phosphate group activates ComE, its cognate response regulator, inducing the expression of comCDE and several other operons (for a review, see Claverys et al, 2006). It has been described that another signal transduction system, designated CiaRH, participates in the early control of competence induction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation